Evaluation and Management of Asymptomatic Bradyarrhythmias - Çinier, Göksel; Haseeb, Sohaib; Bazoukis, Giorgos; Yeung, Cynthia; Gül, E. E. (Current Cardiology Reviews, 2021)
Asymptomatic bradyarrhythmias involving sinus node dysfunction and atrioventicular blocks are frequently noted in clinical practice. Its prevalence is expected to rise as devices that are developed for monitoring cardiac rhythm for longer duration become more widely available. Episodes of bradyarrhythmia that are asymptomatic are considered to have a benign course compared with those that cause symptoms and do not necessitate further treatment. However, in certain cases, they can be a harbinger of future symptoms or cardiac manifestations of systemic diseases. The evaluation and risk stratification of individuals presenting with asymptomatic bradyarrhythmias is important not only for preventing implantation of unnecessary permanent pacing devices but also for reducing significant morbidity by implementing proper treatment as required. In this article, we will review the current evidence on the pathophysiology, diagnosis, evaluation and management of patients with asymptomatic bradyarrhythmias.
Keywords: sinus node dysfunction